Information Retrieval Technology : 12th Asia Information Retrieval Societies Conference, AIRS 2016, Beijing, China, November 30 - December 2, 2016 : proceedings /: 12th Asia Information Retrieval Societies Conference, AIRS 2016, Beijing, China, November 30 - December 2, 2016 : proceedings. ([2016]) - Unknown
No abstract available